Agricultural Landscape Stability and Sustainable Land Management - Cao, Yu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the theme of agricultural landscape stability and sustainable land management, including the ecosystem service values of agricultural landscapes, the development of multifunctional agricultural landscapes, protection of agricultural landscapes, reform of rural land ownership, comprehensive rural development, and remote sensing monitoring of agricultural landscapes.